THE POLITENESS STRATEGIES APPLIED BY STUDENTS IN THE CONTEXT OF CLASSROOM IN VOCATIONAL SCHOOL - Muliadi, Nyoman Rini; Ratminingsih, Ni Made; Marsakawati, Ni Putu Era (Undiksha Press, 2023)
This study has the purpose to explore the politeness strategies of students in a vocational school, how the teachers and students apply the politeness strategies, and the implication of politeness strategies applied to the student’s good character improvement. Descriptive qualitative research was applied in this study which explored the phenomena of politeness in the teaching-learning process. There were 16 classes which consisted of 464 students of XI grade in one of the vocational schools in Buleleng Bali as the participants of this research. 140 students from the hospitality department and 10 teachers were taken as samples for this study. The sources of the primary input were the teachers’ and students’ interactions in the classrooms which were observed and recorded. Ten transcriptions were collected from the observations of ten teachers observed when they taught in the Tourism Department. These transcriptions then were analyzed and reviewed according to Brown and Levinson’s politeness theory in 1987. This research showed that the vocational students applied some types of expressions such as greetings, thanking, addressing, apologizing, and filling. Some expressions or terms were derived from the daily language, which was applied to soften the students’ and teachers’ interactions. All the expressions were grouped into politeness which is positive and negative. The results of this research could be applied as a recommendation for the teachers and students to make the interaction in the classroom effective. Keywords: interaction, language, politeness strategies, teaching-learning process